Strategies to Promote Inclusive Education for High School Students with Different Learning Styles (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Inclusive education is essential for the academic and social development of high school students with different learning styles, and implementing effective strategies can help create a supportive and inclusive learning environment. Plus, prioritizing inclusive education for high school students with different learning styles is also significant their academic success and overall well-being. By understanding the importance of learning styles, using effective strategies, providing teacher training, and creating a supportive school culture, schools can promote an inclusive learning environment that caters to the diverse needs of all students. It is crucial to ensure that every student has the opportunity to thrive academically and socially through inclusive education.